TRADE SECRET PROTECTION VERSUS EMPLOYEE MOBILITY (World Bulletin of Management and Law, 2025)
Trade secret protection and labor mobility often converge, causing employers, workers, and policymakers legal and management conundrums. Here, the author examines the statutory law governing trade secrets, the Uniform Trade Secrets Act (UTSA) and the Defend Trade Secrets Act (DTSA), and how courts balance protection of confidential business information against the right of workers to change employers and use general skill sets. It discusses enforceability of restrictive covenants, standards of evidence for misappropriation claims, and remedies to claimants. The article focuses on compliance strategies effective for employers in practice, best practices during workforce transitions, and policy issues to find a balance for innovation incentives and labor market competition. It makes suggestions to reduce litigation risk while preserving valid interests of both parties.